Statin Use and the Point Prevalence of Antibiotics in Ambulatory Patients with Diabetes in the National Health and Nutrition Examination Survey (NHANES) 2003-2012 - Sumaiah J. Alarfaj; Alexandra Perez; Nathan R. Unger (MDPI AG, 2019)
In patients with diabetes, the risk of infections is increased, hypothesized to be due to alterations in the immune system, among other changes. The pleotropic effects of statins have been investigated to assess their role in reducing the risk of infection and infection-related outcomes with varying results. The aim of this study is to determine if the use of statins is associated with a decrease in the point prevalence of oral antibiotic use in ambulatory patients with diabetes. Using data from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2012, all adult patients diagnosed with diabetes were analyzed. Patients were grouped into those who were prescribed statins and those who were not. Oral antibiotic use between the two groups was compared. Data were standardized to national estimates. A total of 3240 patients with diabetes were identified, with 1575 statin users and 1665 non-statin users. After controlling for baseline socio-demographic and clinical variables, the overall point prevalence of oral antibiotic use in diabetes population was 3.5% with no difference between statin users and non-statin users (2.9% vs. 4%, p = 0.116). Based on the results of this study, the use of statins in patients with diabetes was not associated with a reduction in the point prevalence of antibiotic use.